Colorectal Lymphoma: A Review - Gay, Nathan D.; Chen, Andy; Okada, Craig Y. (Clinics in Colon and Rectal Surgery, 2018)
Non-Hodgkin lymphoma (NHL) that primarily involves the colon is rare and should be distinguished from the more common systemic nodal lymphoma. It has unique clinical expectations and management consideration. Different histologic subtypes of NHL involve the colon, which varies in the clinical behavior and likelihood of obtaining durable remissions with treatment. This article will review the current understanding of the different histologic subtypes of primary colorectal lymphoma and propose management algorithms.
Keywords: primary colorectal lymphoma; extranodal; gastrointestinal; large bowel